Clinical characteristics and prognosis of Korean patients with hepatocellular carcinoma with respect to etiology - Wonjoon Jang; Hye Won Lee; Jae Seung Lee; Beom Kyung Kim; Seung Up Kim; Jun Yong Park; Sang Hoon Ahn; Do Young Kim (Korean Liver Cancer Association, 2022)
Background/Aim The profile of patients with hepatocellular carcinoma (HCC) has changed globally; the role of etiology in predicting prognosis of HCC patients remains unclear. We aimed to analyze the characteristics and prognosis of Korean patients with HCC according to disease etiology. Methods This retrospective observational study included patients diagnosed with HCC between 2010 and 2014 in a single center in Korea. Patients with HCC aged <19 years old, had coinfection with other viral hepatitis, had missing follow-up data, were Barcelona Clinic Liver Cancer stage D, or died before 1 month were excluded. Results A total of 1,595 patients with HCC were analyzed; they were classified into the hepatitis B virus (HBV) group (1,183 [74.2%]), hepatitis C virus (HCV) group (146 [9.2%]), and non-B non-C (NBNC) group (266 [16.7%]). The median overall survival of all patients was 74 months. The survival rates at 1, 3, and 5 years were 78.8%, 62.0% and 54.9% in the HBV group; 86.0%, 64.0%, and 48.6% in the HCV group; and 78.4%, 56.5%, and 45.9% in the NBNC group, respectively. NBNC-HCC has a poorer prognosis than other causes of HCC. Survival was significantly longer in the HBV group with early-stage HCC than in the NBNC group. Furthermore, survival was shorter in patients with early-stage HCC and diabetes mellitus (DM) than in those without DM. Conclusions The etiology of HCC affected clinical characteristics and prognosis to some extent. NBNC-HCC patients showed shorter overall survival than viral-related HCC patients. Additionally, the presence of DM is an additional important prognostic factor in patients with early-stage HCC.